Ethnobotanical Study on Medicinal Plants Used by the Ethnic People of Khagrachhari District, Bangladesh - Sajeeb, BK; Uddin, Mohammad Zashim; Bachar, Ritesh; Bachar, Sitesh C (Dhaka University Journal of Pharmaceutical Sciences, 2022)
The present study deals with important ethnopharmacological information, both in qualitative and quantitative manners on medicinal plants of Khagrachhari district of Bangladesh. The survey was conducted in a period of six months from January 2016 to June 2016 and was interviewed among 155 ethnic people including tribal, Bengalis and 14 traditional health practitioners of eight upazillas in open and semi structured form. The most of the interviewers were Chakma (82%), Marma (8%) and the rest were Tripura (2%) and Bengalis (8%). The total ethnomedicinal plant species was 94, among them 92 were angiosperms, one was gymnosperm and one fern. The plant species belonging to 44 families and 86 generas are used to treat about 53 types of ailments. The different life forms among the species are 28 herbs, 25 trees, 24 shrubs and 17 climbers. The survey showed that the most commonly used plant part was leaves (34.55%) and the most frequent method of preparation was extraction (39.18%) against different ailments. The major treatment options of the medicinal plants of Khagrachhari hilly areas are identified from the study and recommended to take immediate measures for conservation of traditional knowledge of the area. This study showed a hopeful perception for future studies, flaking light on taking immediate measures on inventory of medicinal plants of hilly areas, documentation of verbal information, conservation of threatened plant species, sustainable management of risky areas and preservation of traditional knowledge of herbal medicine in Khagrachhari district, Bangladesh. Dhaka Univ. J. Pharm. Sci. 21(2): 217-230, 2022 (December)